Greenfield Inferior Vena Cava Filter Placement Following Acute Pulmonary Thromboembolism. A Case Report - KAWAHARA Eisuke; YAMASA Toshihiko; NISHIMURA Eni; ASHIZAWA Kazuto; MIYAHARA Yoshiyuki; KOUNO Shigeru (Japanese Journal of National Medical Services, 1996)
A 57-year old man was admitted to our hospital with the chief complaints of dyspnea and gen-eral malaise. On admission, his blood pressure was shock level which was not controled by catech-olamine infusion. Findings of electrocardiogram and ultrasound echocardiography strongly sugges-ted pulmonary hypertension. We diagnosed acute pulmonary thromboembolism by means of right heart catheterization and pulmonary angiography. After injection of tissue plasminogen activator (t-PA), the pulmonary artery pressure decreased gradually.On chronic state, venography and CT scan of lower extremities we proceeded demonstrated large thrombolus in the deep vein of right lower extremity. We inplaced the inferior vena cava fil-ter (Greenf ield's filter) to prevent reccurent pulmonary thromboembolism. 症例は, 57歳の男性で呼吸困難を主訴に来院した. 来院時ショック状態であり, 昇圧剤を投与するも血圧コントロールは不良であった. 心電図および心エコー所見より急性肺血栓塞栓症を疑い右心カテーテル検査および肺動脈造影を施行し, 急性肺血栓塞栓症と診断した. 右心房内よりt-PAを投与し, 投与後肺動脈圧は速やかに改善した, 原因検索のため慢性期に下肢CT, 下肢静脈造影を施行したところ, 右下肢深部静脈内に広範な血栓を認めた. この血栓が急性肺血栓塞栓症の原因と考え, 再発予防のため下大静脈フィルターを挿入し, 以後再発を認めていない.